2009
DOI: 10.1016/j.abb.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxylation is the CYP-dependent and retinoid-inducible leukotriene B4 inactivation pathway in human and mouse skin cells

Abstract: Metabolic inactivation of leukotriene B4 (LTB4) is an innate mechanism to resolve tissue inflammation. We studied the nine Cyp4f genes in the mouse genome, measuring cutaneous transcript levels by real-time polymerase chain reaction, and LTB4 metabolism in mouse and human skin. Transcripts arising from Cyp4f13 and 4f16 ranked most abundant, Cyp4f14, 4f17, and 4f37 ranked least abundant, and Cyp4f18 and 4f39 ranked intermediate. Those from Cyp4f15 and Cyp4f40 were highly variable or too low to measure in some a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(52 reference statements)
0
13
1
Order By: Relevance
“…Strobel and coworkers found that human keratinocytes can ω-hydroxylate LTB4 and that this activity is increased following induction of CYP4F2, CYP4F3A, and CYP4F3B at both the transcript and protein levels by atRA activation of RXR, although the nuclear receptor partner of RXR remains unidentified (Kalsotra et al, 2008). A later study also confirmed that topical administration of retinoids to human skin samples enhanced CYP4F-mediated LTB4 ω-hydroxylation, suggesting one way by which retinoid therapy might exert its anti-inflammatory effects in disorders such as psoriasis and atopic dermatitis (Du, Yin, Morrow, Strobel, & Keeney, 2009). Induction of CYP4F2 has been found to proceed through other pathways in human hepatocytes and HepG2 cells, as well.…”
Section: ω-Hydroxylases In Inflammationmentioning
confidence: 79%
“…Strobel and coworkers found that human keratinocytes can ω-hydroxylate LTB4 and that this activity is increased following induction of CYP4F2, CYP4F3A, and CYP4F3B at both the transcript and protein levels by atRA activation of RXR, although the nuclear receptor partner of RXR remains unidentified (Kalsotra et al, 2008). A later study also confirmed that topical administration of retinoids to human skin samples enhanced CYP4F-mediated LTB4 ω-hydroxylation, suggesting one way by which retinoid therapy might exert its anti-inflammatory effects in disorders such as psoriasis and atopic dermatitis (Du, Yin, Morrow, Strobel, & Keeney, 2009). Induction of CYP4F2 has been found to proceed through other pathways in human hepatocytes and HepG2 cells, as well.…”
Section: ω-Hydroxylases In Inflammationmentioning
confidence: 79%
“…The specific expression of CYP4F3A in neutrophils, and its high activity for LTB 4 , suggests that this is a specialized function of the enzyme. CYP-dependent ω-hydroxylation and inactivation of LTB 4 is induced by retinoids in skin cells and might contribute to the beneficial effects of retinoids in the treatment of inflammatory skin diseases (Du, Yin, Morrow, Strobel, & Keeney, 2009;Kalsotra et al, 2008). CYP4F enzymes are also expressed in neurons and glia, and LTB 4 hydroxylase activity limits neuroinflammation in mouse models (Sehgal et al, 2011).…”
Section: Ltb 4 Inactivationmentioning
confidence: 99%
“…Du et al (2009) reported the expression in the CD-1 mouse skin of the following CYPs on the RNA level: Highest expression: Cyp4f13 and 4f16 , intermediate: Cyp4f18 and 4f39 , low: Cyp4f14, 4f17, 4f37 , highly variable (in some animals below detection): Cyp4f15 and Cyp4f40 . The expression of additional CYPs ( Cyp1a1, Cyp1b1, Cyp2e1 ) was observed in the skin of C57BL/6J mice by Flowers et al (2011).…”
Section: Xenobiotica-metabolizing Enzymes In the Mouse Skinmentioning
confidence: 99%
“…Increases of moue skin enzymatic activities were reported for the following agents and the following activities: TCDD: AHH, EROD (Pohl et al 1976), β-naphthoflavone: ECOD (Pendlington et al 1994), coal tar: AHH, ECOD (Das et al 1985), dexamethasone: AHH (Briggs and Briggs 1973), EROD, PEROD, para-nitrophenol hydroxylase, and erythromycin N -demethylase (Jugert et al 1994), retinoic acid: LTB4 hydroxylation (Du et al 2009). …”
Section: Xenobiotica-metabolizing Enzymes In the Mouse Skinmentioning
confidence: 99%
See 1 more Smart Citation